Benign Prostat Hyperplasia : a review - Alghani, Sulthan Rafi; Sangging, Putu Ristyaning Ayu (Medula, 2024)
The prostate gland is a vital organ that often experiences enlargement, including in a non-malignant form known as Benign Prostatic Hyperplasia (BPH). BPH, which is common in elderly men, is a leading cause of medical intervention in men over 60 years of age and affects quality of life. Epidemiology of BPH, with a prevalence reaching 70-90% in men over 60 years. Although exact data in Indonesia is not yet available, leading hospitals report BPH cases with an average age of sufferers around 66-67 years. Symptoms of BPH, such as difficulty urinating and other clinical complaints, can affect the sufferer's quality of life. Risk factors, including age, family history, obesity, employment history, and diabetes. Prevention and education are also a major concern, with an emphasis on healthy eating patterns, physical activity, reducing caffeine and alcohol consumption, and daily behavior to minimize BPH symptoms. Potential complications include urinary tract obstruction which can lead to infection and even kidney failure if left untreated.